New sophistry: self‐deception in the nursing academy. (20th May 2016) - Garrett, Bernard M.
Abstract: In this essay, I advance an argument against the expansion and acceptance of postmodern metaphysical antirealist ideologies in the development of nursing theory in North America. I suggest mystical theoretical explanations of care, the rejection of empirical epistemology, and a return to divinity in nursing represent an intellectual dead end, as these ideas do little to help resolve real‐world health issues and also negate the need for the academic discrimination of bad ideas. I examine some of the philosophical foundations of nursing theory and deconstruct some of the more preternatural theories that have become established as the dominant conventional wisdom in the academy. It is argued that this can be characterized as a form of self‐deception, and overall has had a negative impact on advancement of the nursing profession and public health care. Reasons behind the widespread acceptance of these irrational theoretical stances in nursing and the ongoing support for mystical therapeutic interventions are explored.